2003
DOI: 10.1053/jlts.2003.50143
|View full text |Cite
|
Sign up to set email alerts
|

Different immunosuppressive regimens and recurrence of primary sclerosing cholangitis after liver transplantation

Abstract: Primary sclerosing cholangitis (PSC) is the fourth leading diagnosis in liver transplant recipients in the UnitedStates. The disease is known to recur in 15% to 30% of liver transplant recipients. We set out to investigate how different immunosuppression regimens affected natural history of PSC after liver transplantation at our center. We reviewed records of all patients who underwent a liver transplantation at our institution in between 1988 and 2000 and had a diagnosis of PSC at the time of liver transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 20 publications
6
95
2
Order By: Relevance
“…[158][159][160][161] The reported frequency of recurrent PSC ranged from 1% to 33%, the variation related in part to differences in diagnostic criteria, duration of follow up, and rigor with which the diagnosis is sought. 150,[162][163][164][165][166] Factors associated with recurrence were steroid-resistant rejection, OKT3 use, preservation injury, ABO incompatibility, cytomegalovirus infection, lack of history of colectomy, male sex, and donor-recipient gender mismatch, but not specific calcineurin inhibitor use or frequency of rejection. [162][163][164][165][166][167] A critical issue is whether recurrence of PSC adversely affects outcome.…”
Section: Session Six Liver Transplantation For Pscmentioning
confidence: 99%
See 1 more Smart Citation
“…[158][159][160][161] The reported frequency of recurrent PSC ranged from 1% to 33%, the variation related in part to differences in diagnostic criteria, duration of follow up, and rigor with which the diagnosis is sought. 150,[162][163][164][165][166] Factors associated with recurrence were steroid-resistant rejection, OKT3 use, preservation injury, ABO incompatibility, cytomegalovirus infection, lack of history of colectomy, male sex, and donor-recipient gender mismatch, but not specific calcineurin inhibitor use or frequency of rejection. [162][163][164][165][166][167] A critical issue is whether recurrence of PSC adversely affects outcome.…”
Section: Session Six Liver Transplantation For Pscmentioning
confidence: 99%
“…150,[162][163][164][165][166] Factors associated with recurrence were steroid-resistant rejection, OKT3 use, preservation injury, ABO incompatibility, cytomegalovirus infection, lack of history of colectomy, male sex, and donor-recipient gender mismatch, but not specific calcineurin inhibitor use or frequency of rejection. [162][163][164][165][166][167] A critical issue is whether recurrence of PSC adversely affects outcome. Instances of graft failure due to recurrent PSC are rare and often confounded by the presence of other forms of liver injury.…”
Section: Session Six Liver Transplantation For Pscmentioning
confidence: 99%
“…1,2 Liver transplantation (LT) is the only existing treatment shown to prolong survival; however, PSC recurs in up to one-third of deceased donor LT and up to two-thirds of living-related donor LT patients. 3,4 The most widely studied pharmacological agent in the treatment of cholestatic liver diseases, ursodeoxycholic acid (UDCA), improves serum liver tests in PSC, but unlike in primary biliary cirrhosis, does not appear to delay disease progression. [5][6][7] Furthermore, a recent large randomised trial has found highdose UDCA to be associated with serious adverse effects (AEs) in patients with PSC.…”
Section: Introductionmentioning
confidence: 99%
“…Steroid-resistant rejection, 5,33 and treatment with muromonab-CD3 are risk factors for the recurrence of primary sclerosing cholangitis after orthotopic liver transplant. In the present patients, we found no effect of acute cellular rejection on recurrent primary sclerosing cholangitis, and the number of steroidresistant episodes of rejection that necessitated antibody treatment was not different between the groups (Table 3).…”
Section: Discussionmentioning
confidence: 99%